The Romantic Development of Classical German Philosophy: From Post-Kantianism to Giorgio Agamben and Jacques Rancière - Hamilton, Paul (Aesthetica Preprint, 2021)
Giorgio Agamben and Jacques Rancière belong to a number philosophers who recently have tried to revive a radical, even revolutionary politics by following post-Kantians in re-conceiving Kant’s idea of the aesthetic in a Romantic vein. This chapter argues that in the process they get us to understand classical German philosophy better through their exploitation of its trademark but crucially unstable construction of a potentially open-ended community of aesthetic judgements. Political reconsideration of the aesthetic is achieved not just through radicalizing Kant’s idea of the “sublime”, as Lyotard attempted some years ago, but by thinking ‘dissensus’ or ‘bare life’, apparently aesthetic categories facilitating a kind of suspension of ideas of law, supposedly essential to political theory, and modelling a new kind of political community. In the process, they define their position through disagreeing with the major critic of Romantic aesthetics and politics, Carl Schmitt.